Functions of students’ scientific and research activity and levels of its organization - Сергеєва, О. А. (Scientific notes of the pedagogical department, 2019)
The article presents approaches to the definition of such key concepts as "science", "scientific research" and "students’ scientific and research activity". The functions of scientific and research activities in US higher educational institutions are analyzed. On the basis of the pedagogical literature analysis, it is found that the main functions of scientific and research activities are: educational (combination of training and preparation for creative work), research (joint research with students and teachers involved, participation in methodological, applied or fundamental research), developmental (development of students' creative abilities, formation of the desire or drive to participate in research activities), disciplinary (independence in activities and reasoning, personal enrichment, ability to use theoretical knowledge in practice), and organizational (cooperation with scientific laboratories, expanding the range of participants in the course of research) ones. The levels of scientific and research activities of US students are analyzed. It is concluded that there are five levels of scientific and research activities. At first level students get tasks and clear instructions, the supervisor explains them the purpose of the task and the expected results. At the second level of scientific and research activities, students receive guidance and necessary information from their supervisor. The third level is initiated by the teacher, but students independently draw conclusions and manage their own activity, determine the best methods and ways of their implementation, take responsibility for the results of their work and its presentation. The fourth level of students’ scientific and research activity is not common in US higher education establishments. In this case, students initiate the research on their own and have no guidance from teachers. At the fifth level, students also initiate research and draw up its plan. But having determined the purpose and plan, it should be agreed with their scientific supervisor, who, if necessary, makes alterations. As a rule, the examples of such activities of the fourth and fifth levels are bachelor or master’s thesis or a scientific article, if we talk about juniors.